2020
DOI: 10.1002/asia.202000071
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Atom Transfer Radical Polymerization by Aggregation‐Induced Emission Technology

Abstract: Aggregation‐induced emission (AIE) technology has been demonstrated to be a facile approach for in‐situ monitoring atom transfer radical polymerization (ATRP). A series of tertraphenyl ethylene (TPE)‐containing α‐bromo compounds were synthesized and applied as ATRP initiators. The photoluminescent (PL) emission of the polymerization system is proved to be sensitive to the local viscosity owing to the AIE characteristics of TPE. Linear relationships between the resulting molecular weight Mn and PL intensity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…They found that the fluorescence quantum yield of AIE-active polystyrene in its aggregated state can be enhanced by increasing the polymer chain length, which is attributed to the higher degree of molecular motion restriction in longer polymer chains [ 41 ]. Similar phenomena have been observed in other systems [ 42 , 43 ]. Interestingly, the polymer film of PHEMA showed a distinct emission color compared to PS and PMMA ( Figure 2 A).…”
Section: Single-fluorophore Aie Polymers Prepared By Controlled Radical Polymerizationsupporting
confidence: 89%
“…They found that the fluorescence quantum yield of AIE-active polystyrene in its aggregated state can be enhanced by increasing the polymer chain length, which is attributed to the higher degree of molecular motion restriction in longer polymer chains [ 41 ]. Similar phenomena have been observed in other systems [ 42 , 43 ]. Interestingly, the polymer film of PHEMA showed a distinct emission color compared to PS and PMMA ( Figure 2 A).…”
Section: Single-fluorophore Aie Polymers Prepared By Controlled Radical Polymerizationsupporting
confidence: 89%
“…It was reported that the emission behavior of AIE-based fluorescent groups was sensitive to the microenvironment; , thus, it could be used to probe parameters such as the molecular weight and viscosity. To investigate the fluorescence properties of AIEgen attached to polymers, the emission behavior of TPE-PMMA was tested under different conditions (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the information was not fully provided for the polymerization of MMA, but the authors indicated a poorly controlled polymerization. Recently, well-controlled ATRP polymerizations of styrene and tert -butyl acrylate were also reported under thermal conditions, but only broadly distributed poly­(methyl methacrylate) (PMMA) was obtained under similar conditions . Because methacrylates represent one of the most important monomers, it is desirable to prepare well-defined poly­(methacrylate)­s and investigate the effect of such an AIE group in the photocatalyzed ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the advantages of AIEgens, Pang group incorporated TPE into the initiators for ATRP (Figure 2B). [ 43 ] In the bulk polymerization for a series of monomers (such as styrene, methyl methacrylate, and tert ‐butyl acrylate) via ATRP using the AIE initiators, both the fluorescence photos and the fluorescence spectra showed the gradual increasing of fluorescence intensity. For polymerization of tert ‐butyl acrylate with AIE‐active TPE‐3 initiator (Figure 2C), a rapid increase of emission intensity began to appear since the monomer conversion rate reached 33% and the emission increase slowed down after conversion above 80% (Figure 2D,E).…”
Section: Polymerization and Dissolution/swellingmentioning
confidence: 99%
“…B) Schematic illustration of ATRP polymerization using AIEgens as initiators, C) ATRP polymerization process of tert-butyl acrylate using TPE-3 as initiator, D) fluorescent photos of reaction system at different conversions taken under 365 nm UV irradiation,E) PL spectra of the polymerization mixture at corresponding conversions, and F) relationship of M n with PL intensity. Reproduced with permission [43]. Copyright 2020, Wiley-VCH GmbH.…”
mentioning
confidence: 99%